1998
DOI: 10.1037/1076-898x.4.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Perspective information in a cockpit as a target acquisition aid.

Abstract: In a simulator experiment, the potential benefits of perspective radar displays for situation awareness support were investigated. A target acquisition task was used in which fighter pilots were required to locate and intercept a target. The pilots were supported by a conventional plan-view radar display, or by two types of perspective exocentric radar displays—with outside-in or inside-out motion reference. Task performance was measured in terms of target acquisition time, tracking accuracy, and workload. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For instance in military aviation, efforts have examined the design and evaluation of novel displays to help pilots more efficiently develop and maintain SA (van Breda & Veltman, 1998;Williams, 2000). In commercial aviation, studies have investigated the effect of automation on aircrew communication and co-ordination (Field & Harris, 1998).…”
Section: Situation Awarenessmentioning
confidence: 99%
“…For instance in military aviation, efforts have examined the design and evaluation of novel displays to help pilots more efficiently develop and maintain SA (van Breda & Veltman, 1998;Williams, 2000). In commercial aviation, studies have investigated the effect of automation on aircrew communication and co-ordination (Field & Harris, 1998).…”
Section: Situation Awarenessmentioning
confidence: 99%
“…Across an array of tasks, a number of studies have found benefits for 3D perspective over 2D (Bemis, Leeds, & Winer, 1988;Ellis, McGreevy, & Hitchcock, 1987;Hickox & Wickens, 1999 (Andre, Wickens, Moorman, & Boschelli, 1991;Baumann, Blanksteen, & Dennehy, 1997;Burnett & Barfield, 1991;Haskell & Wickens, 1993;Van Breda & Veltman, 1998;Wickens, Liang, Prevett, & Olmos, 1996;Wickens & Prevett, 1995), and still other studies have found 2D superior to 3D (Boyer, Campbell, May, Merwin, & Wickens, 1995;Boyer & Wickens, 1994;O'Brien & Wickens, 1997;Wickens, Campbell, Liang, & Merwin, 1995;Wickens & May, 1994;Wickens, Miller, & Tham, 1996). The details of tasks and interfaces vary widely in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the empirical evidence supporting the use of 3-D displays is decidedly mixed, and Andre and Wickens (1995) caution that sometimes "users want what's not best for them." Across an array of tasks, many studies have found benefits for a 3-D perspective over a two-dimensional (2-D) perspective (Andre et al, 1991;Bemis, Leeds, and Winer, 1988;Burnett and Barfield, 1991;Ellis, McGreevey, and Hitchcock 1987;Haskell and Wickens, 1993;and Van Breda and Veltman, 1998). Other studies have found rough parity (Wickens et al, 1996), and still other studies have found 2-D superior to 3-D (Boyer et al, 1995;O'Brien and Wickens, 1997;Ware and Lowther, 1997).…”
Section: Introductionmentioning
confidence: 99%